Seaweed diversity and community structure on the west coast of Aceh, Indonesia - ERNIATI ERNIATI; ERLANGGA ERLANGGA; YUDHO ANDIKA; MULIANI MULIANI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Erniati, Erlangga, Andika Y, Muliani. 2023. Seaweed diversity and community structure on the west coast of Aceh, Indonesia. Biodiversitas 24: 2189-2200. One of the commodities that continues to be developed by the Indonesian government in fisheries is seaweed. The potential of seaweed as a food ingredient in Aceh is very abundant. However, diversity and community structure of seaweeds on the west coast of Aceh have not been studied much. Therefore, this study has been carried out to assess the diversity and community structure of seaweeds on the west coast of Aceh based on transect method. Sampling has been carried out in all districts/cities (6 districts and 1 city) of west coast of Aceh. Altogether, a total of 50 species have been identified; of which, maximum number of species belongs to Phaeophyta (21 species) followed by Chlorophyta (16 species) and Rhodophyta (13 species). The estimated value of diversity (H'), uniformity (E), and dominance (D) index is 1.02, 0.50 and 0.51 respectively. Based on the univariate diversity indices analysis, it has been found that seaweed on the west coast of Aceh is in the moderate category. Furthermore, the water quality parameters revealed the existence of conducive environmental conditions for the growth and life of seaweed. So, it is proposed that use of appropriate seaweed culture techniques can be carried out on the west coast of Aceh to able to make Aceh a seaweed center in Indonesia.